Pengaruh Likuiditas, Solvabilitas, Dan Aktivitas Terhadap Kinerja Keuangan Pada Perusahaan Farmasi Yang Terdaftar Di BEI - Sulthon badar Al rahman; Dedi Suselo (CV ODIS, 2022)
This study aims to examine the variables of liquidity, solvency, and activity on the financial performance of pharmaceutical companies listed on the IDX for the period 2019 to 2021. The population in this study were 7 pharmaceutical companies included in the Islamic stock index group. The data analysis method in this study uses multiple linear regression analysis (multiple regression). The hypothesis test used in this research is the coefficient of determination test, t test, and F test. The result of the coefficient of determination R Square (R2) is 0.678 or 67.8%. This figure can be interpreted that the ratio of liquidity, solvency, and ratios have a significant effect on financial performance of 67.8% and 32.2% is explained by other variables outside the research model. The results of the partial statistical test of the liquidity ratio have no significant effect on financial performance, while the solvency ratio and activity ratio have a significant effect on financial performance. Simultaneously the liquidity ratio, solvency ratio, and activity ratio have a significant effect on financial performance.